POLITICAL FRAMEWORKS FOR TRIBAL EMPOWERMENT IN INDIA: SUCCESSES, CHALLENGES, AND RECOMMENDATIONS - Bhatnagar, Arti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the political policies and programs implemented for the socio-economic development of tribal communities in India, recognized as Scheduled Tribes (STs). Despite constitutional safeguards and targeted initiatives, tribal communities continue to face significant socio-economic challenges. This research reviews key policies such as the Tribal Sub-Plan (TSP), Vanbandhu Kalyan Yojana, Eklavya Model Residential Schools (EMRS), and the Forest Rights Act. It assesses their effectiveness, identifies persistent barriers, and offers recommendations for improvement. The findings indicate that while there has been notable progress in areas like education and economic empowerment, the overall impact is uneven due to administrative inefficiencies, lack of awareness, and inadequate implementation. Recommendations emphasize strengthening policy execution, enhancing administrative efficiency, increasing awareness and participation, improving infrastructure, and leveraging technology for better service delivery. Additionally, the study highlights the need for robust monitoring and evaluation mechanisms to ensure the sustained success of development initiatives. By addressing these challenges and fostering greater community involvement, the Indian government can enhance the socio-economic conditions of tribal communities. This research underscores the importance of continuous policy refinement and inclusive development strategies to achieve long-term improvements for India’s tribal populations.